Social Wellbeing as a Criterion of Structural Policy Efficiency; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Gasanov M. A. Magerram Ali Ogly (2016, 2016)
Title screen